Execution of Hibah Amanah as an Instrument of Islamic Property Management in Malaysia - Halim, Akmal Hidayah; Ahmad Bustami, Tajul Aris (Kanun: Jurnal Undang-undang Malaysia; Vol 29 No 2 (2017): KANUN: Jurnal Undang-undang Malaysia Volume 29 Number 2 July 2017, 2017)
The use of hibah amanah has become an alternative in the Islamic property management in Malaysia. Hibah amanah enables a donor to have control over his/her property during his/her lifetime and the donee or beneficiary can only benefit from it upon the death of the donor. On the surface, hibah amanah seems to be inconsistent with the Islamic rules of hibah , wills, trust and inheritance as the donor does not give up his rights or possession of the property during his lifetime even though the donee has the legal capacity to own and manage his property. Hence, this article seeks to examine the implementation of hibah amanah by Muslims in Malaysia and its legality as an instrument of property distribution in Islamic law so that the rights of every entitled person in one's estate may be ascertained and protected. Keywords: hibah , trust, wills, inheritance, hibah ruqba, Muslim